The Influence of Self-Reported Tobacco Use on Baseline Concussion Assessments. Issue 3 (10th October 2019) - Roach, Sean P; Houston, Megan N; Peck, Karen Y; Svoboda, Steven J; Kelly, Tim F; Malvasi, Steven R; McGinty, Gerald T; Campbell, Darren E; Cameron, Kenneth L
Abstract: Introduction: Baseline symptom, balance, and neurocognitive scores have become an integral piece of the concussion management process. Factors such as sleep, learning disorders, fitness level, and sex have been linked to differences in performance on baseline assessments; however, it is unclear how tobacco use may affect these scores. The objective of this study was to compare baseline concussion assessment scores between service academy cadets who use and do not use tobacco. Methods: Cadets completed a standard battery of concussion baseline assessments per standard of care and were classified into two groups: tobacco users ( n = 1, 232) and nonusers ( n = 5, 922). Dependent variables included scores on the Balance Error Scoring System, Standardized Assessment of Concussion, Immediate Post-Concussion Assessment and Cognitive Testing (ImPACT), Brief Symptom Inventory-18, and Brief Sensation Seeking Scale (BSSS). Separate Mann–Whitney U-tests were used to compare all baseline assessment scores between groups with an adjusted P -value < 0.004. Results: Cadets that used tobacco performed significantly worse on the impulse control ( P < 0.001) section of the ImPACT, reported greater ImPACT symptom severity scores ( P < 0.001), and were more likely to take risks as measured by the BSSS ( P < 0.001). No differences were detected for Balance Error Scoring System, Standardized Assessment of Concussion, Brief Symptom Inventory-18, and Sport Concussion Assessment Tool-3 symptom scores, verbal memory, visual memory, visual-motor speed, or reaction time on the ImPACT ( P > 0.004). Conclusions: Tobacco users performed significantly worse than tobacco nonusers on the impulse control section of the ImPACT, reported greater symptom severity scores on the ImPACT, and were more likely to take risks as measured by the BSSS. Despite statistical significance, these results should be interpreted with caution, as the overall effect sizes were very small. Future research should examine the influence of tobacco use on recovery post-concussion.